2017
DOI: 10.1093/jpepsy/jsx082
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Coping and Depressive Symptoms Partially Explain the Association Between Family Stress and Pain-Related Distress in Youth With IBD

Abstract: Results suggest that family stress can place children at risk for greater expressed pain-related distress through effects on coping and depressive symptoms. Addressing psychosocial difficulties is important for closing the gap between disability and health in youth with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…This distribution is reflective and representative of the population distributions of pediatric IBD 10 and comparable with other study samples. 28,35 The mean time since diagnosis was 37.42 months (SD = 33.69, range = 2–153). Most of the children had an inactive disease status at the time of study participation (n = 49, 81.7%) for those with an active disease status (n = 11, 18.3%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This distribution is reflective and representative of the population distributions of pediatric IBD 10 and comparable with other study samples. 28,35 The mean time since diagnosis was 37.42 months (SD = 33.69, range = 2–153). Most of the children had an inactive disease status at the time of study participation (n = 49, 81.7%) for those with an active disease status (n = 11, 18.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these findings are largely in line with and extend previous evidence stressing the relevance of caregiver context in understanding HRQOL. 14,15,27,28 Furthermore, the differences found between youth and parent perspectives on family functioning and the subsequent diverse influence on youth's outcomes highlights the importance of soliciting multiple perspectives of family functioning and underscores how the family system is more than the sum of its parts. 1,21 In particular, the underlying mechanisms explaining youth HRQOL seem more complex from a parental perspectives with their view on family cohesion being associated with youth's HRQOL, through their contribution in explaining pain symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when examining specific domains of family functioning, worse family affective involvement (i.e., degree of family interest and involvement with one another) was positively correlated with parent-reported adolescent depressive symptoms, while better family problem-solving was negatively correlated with self-reported adolescent depressive symptoms [ 41 ]. Additionally, family stress has demonstrated significant, positive associations with youth self-reported depressive symptoms [ 44 ]. Although a direct comparison cannot be made, these results suggest that relationships between family functioning and adolescent depressive symptoms likely depend on specific domains of functioning as opposed to more global measures.…”
Section: Family Functioningmentioning
confidence: 99%
“…With regards to disease activity, higher family HRQOL was significantly associated with decreased youth disease activity [ 39 ], and general family dysfunction demonstrated a positive, significant relationship to pain/fatigue and the frequency of bowel movements [ 36 ]. Reed–Knight and colleagues [ 44 ] examined IBD pain-specific factors in relation to family stress and found that greater family stress was positively related to youths’ pain-related expressions of distress and passive pain coping. Across studies, results demonstrate a consistent relationship between aspects of family functioning and a variety of IBD outcomes, characterized by better family functioning and improved disease functioning.…”
Section: Family Functioningmentioning
confidence: 99%